2012
DOI: 10.1073/pnas.1210684109
|View full text |Cite
|
Sign up to set email alerts
|

Role of the irreplaceable residues in the LacY alternating access mechanism

Abstract: Few side chains in the galactoside/H + symporter LacY (lactose permease of Escherichia coli) are irreplaceable for an alternating access mechanism in which sugar binding induces closing of the cytoplasmic cavity and reciprocal opening of a periplasmic cavity. In this study, each irreplaceable residue was mutated individually, and galactoside-induced opening or closing of periplasmic or cytoplasmic cavities was probed by site-directed alkylation. Mutation of Glu126 (helix IV) or Arg144 (helix V), which are esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Although earlier studies suggested by implication that Tyr236, Glu269, and His322 may be involved in H + transport, it is now apparent that these side chains are clearly ligands to the galactopyranoside ring [19]. Although mutation of these residues causes the periplasmic side of LacY to open spontaneously [136], there is no direct evidence that they are involved in H + translocation, although it is conceivable that one or more may play a dual role in the transport mechanism. It is also notable that every residue in LacY has been subjected to site-directed mutagenesis, and, with the exception of the irreplaceable residues described, each of which has a known function, there are no other side chains in the protein which are absolutely required for lactose/H + symport.…”
Section: 1mentioning
confidence: 75%
“…Although earlier studies suggested by implication that Tyr236, Glu269, and His322 may be involved in H + transport, it is now apparent that these side chains are clearly ligands to the galactopyranoside ring [19]. Although mutation of these residues causes the periplasmic side of LacY to open spontaneously [136], there is no direct evidence that they are involved in H + translocation, although it is conceivable that one or more may play a dual role in the transport mechanism. It is also notable that every residue in LacY has been subjected to site-directed mutagenesis, and, with the exception of the irreplaceable residues described, each of which has a known function, there are no other side chains in the protein which are absolutely required for lactose/H + symport.…”
Section: 1mentioning
confidence: 75%
“…1 and 2), are clearly ligands to the galactopyranoside. Although mutation of these residues causes the periplasmic side of LacY to open spontaneously (53), there is no direct evidence that they are involved in H + translocation, although it is conceivable that they may play a dual role in the transport mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Although His322 is clearly involved in affinity for galactosides, it has been suggested that it is also involved in H + translocation (54). Moreover, the notion has been put forward that structural water coordinated within a triad between His322, Tyr236, and Glu269 (two additional irreplaceable residues) may act as a cofactor for binding and galactoside/H + symport by forming a hydronium ion intermediate during turnover (54,55). In this regard, an analogous situation is apparent in PepT Gk where Glu35, which corresponds to His322 in LacY, is not a direct substrate ligand.…”
Section: An Overall Mechanism For Coupling In Lacymentioning
confidence: 99%